Perceptions on autism and child-rearing practices of mothers of autistic Filipino children - Corpus, Carmelina de Perio (1986)
This empirical research deals with the mothers' perceptions of their autistic children's autism/handicap, behaviors, abilities/potentials and their child-rearing practices along: control of aggresssive behavior; encouragement of reciprocity; appropriate closeness; acceptance of emotional complexities; and comfort in perceiving and meeting the child's physical needs. It also sought to determine the differences among the respondents grouped according to age, educational qualification, type of employment, number of children in the family, combined monthly income, closeness of family, number of hours spent with the child, and number of years in school.The study likewise determines the correlation between mothers' frequency of contacts and their child-rearing practices and perceptions on autism and their child-rearing practices.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Keywords: Autism -- Philippines; Children -- Management. -- Philippines